MANAGING THE PANDEMIC IN CARE HOMES – OLDER PEOPLE’S PERSPECTIVE - Zemaitaityte, Irena; Radziuliene, Veslava (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
The ageing population and the challenges it poses are becoming more and more pressing, both in Lithuania and in other European countries. This requires constant attention from researchers and institutions providing social services and education activities. A new challenge is the Covid - 19 pandemic, which has resulted in nursing homes banning visits to residents and restricting educational activities in order to protect the elderly. Residents were not allowed to see relatives and friends. The pandemic and the quarantine imposed in Lithuania caused stress and anxiety for the residents and the negative social consequences are still being felt even after the pandemic. Nine semi-structured interviews were carried out to reveal the attitudes of older people towards the management of the pandemic in care institutions and the peculiarities of communication in care homes during the quarantine. The research revealed that during quarantine, lonely older people were sensitive to a lack of opportunities for social communication, and felt a lack of closeness among people. As a result of the quarantine regime lonely older people felt unfulfilled, lost the ability to realize themselves through certain activities.